BODIPY dyes for singlet oxygen and optical limiting applications - Harris, Jessica (Rhodes University, Faculty of Science, Department of Chemistry, 2018)
A series of structurally related BODIPY dyes were synthesised and characterised. Their photophysical properties were studied in order to determine whether they would be suitable candidates for use as photosensitisers in the photodynamic therapy (PDT) treatment of cancer. The synthesis of two highly fluorescent BODIPY cores was achieved via the acid-catalysed condensation of a pyrrole and a functionalised aldehyde. In order to promote intersystem crossing, and hence improve the singlet oxygen generation of these dyes, bromine atoms were added at the 2,6-positions of the BODIPY core. These dibrominated analogues showed good singlet oxygen quantum yields, and excellent photostability in ethanol. In order to red-shift the main spectral bands of the BODIPY dyes towards the therapeutic window, vinyl/ styryl groups were introduced at the 3-, 5-, and 7-positions via a modified Knoevengal condensation reaction. The addition of vinyl/ styryl groups to the BODIPY core caused an increase in fluorescence quantum yield as well as a decrease in singlet oxygen quantum yield with respect to the dibrominated analogues. However, two of the red-shifted BODIPY dyes still showed moderate singlet oxygen quantum yields. The use of BODIPY dyes in nonlinear optics (NLO) was explored. The nonlinear optical characterisations and optical limiting properties of a series of 3,5-dithienylenevinylene BODIPY dyes were studied, both in dimethylformamide (DMF) solution and when embedded in poly(bisphenol A carbonate) (PBC) as thin films. The 3,5-dithienylenevinylene BODIPY dyes showed typical nonlinear absorption behaviour, with reverse saturable absorption (RSA) profiles, indicating that they have potential as optical limiters. The second-order hyperpolarizability (Y), and third-order nonlinear susceptibility (/m[/(3)]) values are also reported for these dyes. The optical limiting values of one of the BODIPY dyes in solution, and two of the BODIPY-embedded PBC films, were below the maximum threshold of 0.95 J-cm-2. The effect of addition of substituents on the electronic structure of the BODIPY dyes was investigated using TD-DFT calculations. The calculated trends closely followed those determined experimentally.
Keywords: Photosensitizing compounds; Active oxygen -- Physiological effect; Photochemotherapy; Cancer -- Treatment; Nonlinear optics; BODIPY (Boron-dipyrromethene)